Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infectivity by Viral Load, S Gene Variants and Demographic Factors, and the Utility of Lateral Flow Devices to Prevent Transmission. (11th May 2021) - Lee, Lennard Y W; Rozmanowski, Stefan; Pang, Matthew; Charlett, Andre; Anderson, Charlotte; Hughes, Gareth J; Barnard, Matthew; Peto, Leon; Vipond, Richard; Sienkiewicz, Alex; Hopkins, Susan; Bell, John; et al.
Abstract: Background: How severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infectivity varies with viral load is incompletely understood. Whether rapid point-of-care antigen lateral flow devices (LFDs) detect most potential transmission sources despite imperfect clinical sensitivity is unknown. Methods: We combined SARS-CoV-2 testing and contact tracing data from England between 1 September 2020 and 28 February 2021. We used multivariable logistic regression to investigate relationships between polymerase chain reaction (PCR)-confirmed infection in contacts of community-diagnosed cases and index case viral load, S gene target failure (proxy for B.1.1.7 infection), demographics, SARS-CoV-2 incidence, social deprivation, and contact event type. We used LFD performance to simulate the proportion of cases with a PCR-positive contact expected to be detected using 1 of 4 LFDs. Results: In total, 231 498/2 474 066 (9%) contacts of 1 064 004 index cases tested PCR-positive. PCR-positive results in contacts independently increased with higher case viral loads (lower cycle threshold [Ct] values), for example, 11.7% (95% confidence interval [CI] 11.5–12.0%) at Ct = 15 and 4.5% (95% CI 4.4–4.6%) at Ct = 30. B.1.1.7 infection increased PCR-positive results by 50%, (eg, 1.55-fold, 95% CI 1.49–1.61, at Ct = 20). PCR-positive results were most common in household contacts (at Ct = 20.1, 8.7% [95% CI 8.6–8.9%]), followed by household visitors (7.1% [95% CI 6.8–7.3%]), contacts at events/activities (5.2% [95% CI 4.9–5.4%]), work/education (4.6% [95% CI 4.4–4.8%]), and least common after outdoor contact (2.9% [95% CI 2.3–3.8%]). Contacts of children were the least likely to test positive, particularly following contact outdoors or at work/education. The most and least sensitive LFDs would detect 89.5% (95% CI 89.4–89.6%) and 83.0% (95% CI 82.8–83.1%) of cases with PCR-positive contacts, respectively. Conclusions: SARS-CoV-2 infectivity varies by case viral load, contact event type, and age. Those with high viral loads are the most infectious. B.1.1.7 increased transmission by 50%. The best performing LFDs detect most infectious cases. Abstract : In 2, 474, 066 contacts of 1, 064, 004 SARS-CoV-2 cases, PCR-positive tests in contacts increased with higher index case viral loads, the B.1.1.7 variant and household contact. Children were less infectious. Lateral flow devices detect 83.0-89.5% of infections leading to onward transmission